THE RELATIONSHIP BETWEEN ORGANISATIONAL RESOURCES, CAPABILITIES, SYSTEMS AND COMPETITIVE ADVANTAGE - Alimin Ismadi Ismail,; Raduan Che Rose,; Jegak Uli,; Haslinda Abdullah, (Asian Academy of Management Journal, 2012)
The main objective that business organisations in particular should strive to attain is achieving a competitive advantage position relative to their competitors.. This research empirically examined the importance of and emphasis placed on organisational resources, capabilities and systems in their relationships with competitive advantage. The overall findings indicated significant, positive effects of organisational resources, capabilities and systems collectively on competitive advantage, providing support and corroboration to the resource-based view (RBV). The total variance in competitive advantage accounted for by the multiple linear regression (MLR) model was 56.2%. In short, the findings from this study have not only contributed to the literature on the issue of the relationship between organisational resources, capabilities, systems and competitive advantage, but also provided vital information to both practitioners and policy makers on the subject matter.